Acyclic Quaternary Carbon Stereocenters via Enantioselective Transition Metal Catalysis - Feng, Jiajie (Chem Rev, 2017)
Whereas numerous asymmetric methods for formation of quaternary carbon stereocenters in cyclic systems have been documented, the construction of acyclic quaternary carbon stereocenters with control of absolute stereochemistry remains a formidable challenge. This review summarizes enantioselective methods for the construction of acyclic quaternary carbon stereocenters from achiral or chiral racemic reactants via transition metal catalysis.